FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILIHAN KARIR MAHASISWA S1 AKUNTANSI SEBAGAI AKUNTAN PUBLIK - Vania Susanto; Jeremy Everrell; Nany Chandra Marsetio; Achmad Setyo Hadi (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This research aims to examine the effect of compensation, variety of work experiences, marketability, high turnover, work environment, subjective norms, difficulty to pursue CPA certification, intention to pursue CPA certification, extensive travel and internship experiences on the career choice of undergraduate accounting students as public accountants using theory of planned behavior and motivation theory. The sample was collected by using purposive sampling, resulting in 155 undergraduate students from 3 private universities and 3 public universities in Java Island. Logistic regression analysis is used with the help of SPSS 26. Interviews as a triangulation is conducted to understand the results better. Results show that compensation, subjective norms and intention to pursue CPA certification have a positive influence while high turnover and extensive travel have a negative influence on the career choice of undergraduate accounting students as public accountants. The results of logistic regression also found that variety of work experiences, marketability, work environment, difficulty to pursue CPA certification and internship experiences have no influence on the career choice as a public accountant. This paper has important implications as a reference for future research, for the preparation of the accounting study program curriculum, as interview materials for the recruitment process, and for IAPI to socialize the CPA certification requirements. Keywords: career choice, public accountant, theory of planned behavior, motivation theory